# Replace $n$ sets with two sets (set theoretic equality)

Let $A_0,\dots,A_{n-1}$ be sets for some whole $n>0$.

Take $A'_{0, i} = A_i$ and $A'_{1, i} = \bigcup ( \{ A_0, \ldots A_{n - 1} \} \setminus \{A_i\})$ for $i=0,\dots,n-1$.

Prove (or disprove) $$\bigcup_{i=0}^{n-1} ( A_i \times A_i) = \bigcap_{i=0}^{n-1} \left( (A'_{0, i} \times A'_{0, i}) \cup ( A'_{1, i} \times A'_{1, i}) \right) .$$

-
By $$\bigcup\left(\{A_{0},\ldots, A_{n-1}\}\setminus A_{i}\right),$$ do you mean this: $$\bigcup_{j\neq i}A_{j}.$$ Or do you mean this:$$\left(\bigcup_{j=0}^{n-1}A_{j}\right)\setminus A_{i}.$$ – Unwisdom Mar 13 '14 at 17:44
@Unwisdom: I mean $\bigcup_{j\neq i}A_{j}$. (It can't mean something different.) – porton Mar 13 '14 at 17:46
Your notation is incorrect, then, if that is your meaning: $B\setminus A_i$ is the set of elements of $B$ not in $A_i$. If $B=\{A_1,\dots,A_{n-1}\}$, then $B\setminus A_i$ is the set of $A_j$ that do not belong to $A_i$. In particular, since $A_i\notin A_i$ under standard axioms, we have that $A_i$ is in this difference. – Andrés E. Caicedo Mar 16 '14 at 3:16
@AndresCaicedo: Thanks, corrected. – porton Mar 16 '14 at 12:58

Thanks for the clarification. The result is false in general.

Suppose that $n=4$ and we have the following sets: \begin{eqnarray} A_0&=&\{a,x\}\\ A_1&=&\{b,y\}\\ A_2&=&\{c,x\}\\ A_3&=&\{d,y\}. \end{eqnarray}

Then \begin{eqnarray} A'_{1,0}&=&\{b,c,d,x,y\}\\ A'_{1,1}&=&\{a,c,d,x,y\}\\ A'_{1,2}&=&\{a,b,d,x,y\}\\ A'_{1,3}&=&\{a,b,c,x,y\}. \end{eqnarray}

Now, $\{x,y\}\subseteq\bigcap_{i=0}^{3}A'_{1,i}$, so trivially $$\langle x,y\rangle\in \bigcap_{i=0}^{3}\left( (A'_{0,i}\times A'_{0,i})\cup (A'_{1,i}\times A'_{1,i}) \right).$$

However, no single $A_{i}$ has both $x$ and $y$ as an element, so $$\langle x,y\rangle \not\in\bigcup_{i=0}^{3}(A_{i}\times A_{i}).$$

Thus $$\bigcup_{i=0}^{3}(A_{i}\times A_{i})\not\supseteq\bigcap_{i=0}^{3}\left( (A'_{0,i}\times A'_{0,i})\cup (A'_{1,i}\times A'_{1,i}) \right).$$

For what it's worth, the reverse inclusion is fine. It suffices to show that
$$(A_{i}\times A_{i})\subseteq(A'_{0,j}\times A'_{0,j})\cup (A'_{1,j}\times A'_{1,j})$$ for an arbitrary $i,j$. This is trivial for $i=j$ since $A_i=A'_{0,i}$. For $i\neq j$, it follows from the fact that $A_{i}\subseteq A'_{1,j}$.

-